Comparative Analysis of Data Mining Techniques - kaur, Shaganpreet; Chinu (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the area of research, which means that useful information or knowledge is extracted from previous data. Data mining defines large amounts of data as a process of finding information such as super market data for various technologies used for data mining, such as science, research, medicine, media, web, entertainment and many other areas, which is implemented with various goods, data mining model data warehouses and online analytical resources. Data mining has made a immense advancement in recent year but the problem of lost data has remained a big challenge for data mining algorithms. This paper analyzed the predictive and descriptive techniques such as classification, regression time series analysis ,predication and clustering, summarization, association rules, sequence discovery techniques on the basis of algorithms which is used to predict previously unidentified class of objects.